PENGEMBANGAN MODUL FOKUSKY PARASITOLOGI PADA PROGRAM STUDI PENDIDIKAN BIOLOGI IKIP BUDI UTOMO MALANG - Mistianah, Mistianah; Qomariyah, Ismi Nurul (Jurnal Pendidikan Biologi, 2019)
This study aims to develop a focusky-based module on Paracytology course for Biology Education college students. The type of this research is Research Development (Research and Development). The development of focusky-based module uses the Research and Development (R & D) method with the 4 D model (Define, Design, Develop, and Dessiminate). This research starts from the define stage where at this stage identification of material concepts that must be contained in focusky-based module. Furthermore  design the focusky-based module. After focusky-based module has been designed and created, the development stage is carried out, namely product validation by experts and product testing in the lecture process. The results showed that the validity of the material experts was in valid criteria with the percentage of paracytology modules of 89%, the results of validity by media experts were in valid criteria with the percentage of learning media as much as 88,25%. From the feasibility test, it was concluded that the module is included in the category very good.